Cation‐mediated electrostatic interaction in collagen–integrin complex1. (21st March 2014) - Ansalone, P.; Bottauscio, O.; Manzin, A.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The paper investigates the electrostatic interactions between organic scaffolds, made of collagen, and a specific family of integrin proteins. We focus the attention on a triple‐helical collagen peptide able to specifically recognize the transmembrane protein integrin α2β1, usually involved in cell adhesion processes. The study of molecular adhesion is performed via a boundary element code designed to solve the linearized Poisson–Boltzmann equation. The binding affinity of the two molecular structures is analyzed making reference to the electrostatic complementarity principle. The mediating role of cation Co2+ is also discussed. Copyright © 2014 John Wiley & Sons, Ltd.